Macroclimate and Topography Interact to Influence the Abundance of Divaricate Plants in New Zealand - Lusk, Christopher H.; Wiser, Susan K.; Laughlin, Daniel C. (Frontiers in Plant Science, 2020)
The abundance of the divaricate form in New Zealand has been interpreted as either (a) the response of an isolated flora to cool, dry, Plio-Pleistocene climates; or (b) a defence against large browsing birds (moa) that were extirpated shortly after human arrival during the last millennium. We used patterns of divaricate plant abundance across present-day landscapes to test a novel synthetic hypothesis: that the divaricate form is of most value to plants on fertile soils that attract herbivores, on sites where climatic constraints prevent plants from quickly growing out of the browse zone. This hypothesis predicts that divaricates should be most abundant on terraces (landforms that are both fertile and frost-prone) in cold, dry regions; and should be scarce across all topographic positions in the warmest regions. To address our hypothesis, we first tested the influence of topography on frost regimes and nutrient levels by measuring temperatures and soil total C, N and P at four standard topographic positions at five localities differing widely in macroclimate. We then calculated the proportion of arborescent species with a divaricate form and the proportion of total arborescent cover contributed by divaricates on each of 9,877 relevé plots extracted from the New Zealand National Vegetation Survey databank. We then fitted linear mixed-effect models predicting these response variables as functions of topographic position and climate. Terraces were subject to more frequent and harder frosts than any other topographic position. Topography had no significant influence on total N, but P was higher on terraces and in gullies than on faces or ridges. Frost-free period was the dominant influence on both species representation and cover of divaricates. Divaricates made their largest contributions on terraces in cold, dry regions; as predicted, they were scarce on all topographic positions on sites with frost-free periods > 300 days. Our hypothesis was generally supported, although the effect of topography on divaricate abundance was not as strong as some previous studies led us to expect. The contemporary distribution of the divaricate form across New Zealand landscapes thus appears to be reasonably well explained by the hypothesized interaction of climate and fertility-mediated browsing.